Notes on Narrative Method in Historical Interpretation - K. Michael Hays (Footprint)
These notes are offered as a sketch of interpretive method. I suggest that the writing of architectural history is, or should be, a deeply theoretical sort of symptomatology – an account of how the very forms and experiences of architecture both construct and repress the absent thing we call the social, and are its most material symbolizations. Such an account benefits from an idea and a practice of narrative. Narrative is an ideological production that avoids any copy theories of representation even as it insists on the real, material forms and events that are its subject matter.